Sampling and analysis of iron, steel and other ferrous metals. Methods of analysis. Determination of sulphur. Steel and cast iron: infra-red absorption method after combustion in an induction furnace Part 3.28.2, (31st August 1990) - British Standards Institution,
No abstract available